Multi-objective Optimization of Electricity-Gas-Heat Integrated Energy System Based on Improved NSGA-Ⅱ Algorithm - Meng JIANG; Yu HUANG; Weihan LIAO; Jianlian ZHANG; Youwen ZHANG; Chuangxin GUO (发电技术)
With the development of interaction between electricity, natural gas and heat networks, collaborative optimization of integrated energy system has become a new research focus. An improved NSGA-Ⅱ algorithm was proposed to solve the optimization problem of integrated energy system, which contained multiple objectives and nonconvex constraints, a global Pareto set maintenance method was proposed to improve the search efficiency of Pareto-optimal solutions. Dimensional reduction and dynamic adjustment were applied to improve the probability of finding feasible solutions under high-dimension equality constraints. An example was analyzed to prove the validity of the proposed method.